Chatgpt in enhancing technical writing: Insights of engineering students - Azwin Arif, Abdul Rahim; Nabila, Abdul Malek (Penerbit UMPSA, 2024)
In an age of rapidly evolving educational technology, this research explores the use of ChatGPT to improve technical writing abilities among engineering students. Despite the potential advantages, little study has been conducted on such technologies’ perceived usefulness and ease of use in higher educational settings. The lack of comprehension impedes successfully integrating AI-driven writing technologies into engineering education. This study employs surveys and statistical analysis to evaluate the complex interactions between gender influence, prior AI experience, and students’ intention to utilise ChatGPT in technical writing. The results indicate that gender does not significantly impact perceived usefulness and ease of use. However, prior experience with AI technologies correlates adversely with students’ inclination to use ChatGPT, emphasising the importance of self-efficacy. The findings from the multiple regression analysis revealed that perceived usefulness and ease of use substantially influence students’ behavioural intentions, giving critical insights into the acceptance and use of technology in technical writing assignments. This study adds to the growth of AI integration in engineering education, with significant consequences for educators and policymakers.